Playing on artificial turf may be an advantage for Norwegian soccer teams - Hvattum, L. M. (Journal of Quantitative Analysis in Sports, 2015)
Soccer is as popular as ever, and the sport attracts significant attention from spectators, sponsors, media, and academics. One aspect of the sport that has received relatively little attention, is the effect of the playing surface on the sporting performance of a team. In particular, this paper is concerned with measuring the performance of teams that switch from playing their games on natural grass to playing their games on artificial turf. It is shown that teams, on average, achieve improved results after switching, and that this, at least in part, can be explained by an increased home field advantage.